MULTIPLE CHOICE QUESTIONS IN ASSESSING MEDICAL STUDENTS’ ACHIEVEMENTS IN ENDOCRINOLOGY MODULE IN REFERENCE TO ‘UTILITY’ - Al-Qahtani, Saeed A. (Pakistan Journal of Physiology, 2016)
Background: Usefulness of the MCQs was defined in relations to five factors: validity, reliability, cost, acceptability and educational impact; collectively called ‘utility’. The aim of this study was to use ‘utility’ as a frame of reference to assess the usefulness of the multiple choice questions to measure the performance of 3rd year medical students, Jazan University, in the final exam of Endocrinology module (2013/2014), also to evaluate the validity evidences especially those related to internal structure to support the interpretations and the use of the students’ results. Methods: This study was a retrospective of written pen and paper assessment tool utilizing a sample of 62 of 3rd year medical students in the final exam of Endocrinology module. Seventy single best answer MCQs were used. Test blueprint used as a source of content-related evidence. Students’ results were analysed to measure reliability and standard error of measurement, difficulty and discrimination indices. Results: The quality of the exam was high as indicated with the high reliability, low standard error of measurement and with values of difficulty and discrimination indices in acceptable ranges. The exam was not costly, acceptable, and had an educational impact. Conclusion: Using utility as a reference frame helps in producing high quality MCQs. However, evidences that support the interpretations and use of the students’ results should be considered. Pak J Physiol 2016;12(3):23–6